Posouzení informačního systému v rodinném podniku a návrh změn - Železný, David (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2020)
Tato diplomová práce je zaměřena na posouzení současného stavu informačního systému vybrané společnosti, zabývající se prodejem zahradnických potřeb. Obsahuje teoretické zázemí problematiky informačních systému a řízení jejich efektivnosti a bezpečnosti. Popisuje jednotlivé oblasti zkoumaného informačního systému a jejich nedostatky. Na základě zpracovaných analytických metod a dotazníkového průzkumu navrhuje změny, směřující ke zlepšení stávajícího stavu a snížení nalezených rizik. Realizace návrhů je ekonomicky zhodnocena.

The diploma thesis is focused on assessment of a selected company’s information system, whose field of business is sale of gardening supplies. The thesis comprises theoretical knowledge about information systems and management of their effectiveness and security. It further provides description of the researched information system along with its insufficiencies. Based on the assessed analytical methods and a conducted survey the thesis provides suggestion to the system which aim at improvement of the current conditions and decrease of the detected risks. The implementation of the provided suggestions is evaluated from an economic perspective.
Assessment of Information System Effectiveness in a Family Business and Proposal of Changes
Keywords: Informační systém; data; efektivnost; bezpečnost; analýza rizik.; Information system; data; effectiveness; security; risk analysis.